Competitive engineering a handbook for systems engineering, requirements engineering, and software engineering using Planguage - Gilb, Tom (Butterworth-Heinemann, 2005)
Competitive Engineering documents Tom Gilb's unique, ground-breaking approach to communicating management objectives and systems engineering requirements, clearly and unambiguously. Competitive Engineering is a revelation for anyone involved in management and risk control. Already used by thousands of project managers and systems engineers around the world, this is a handbook for initiating, controlling and delivering complex projects on time and within budget. The Competitive Engineering methodology provides a practical set of tools and techniques that enable readers to effectively design, manage and deliver results in any complex organization - in engineering, industry, systems engineering, software, IT, the service sector and beyond. Elegant, comprehensive and accessible, the Competitive Engineering methodology provides a practical set of tools and techniques that enable readers to effectively design, manage and deliver results in any complex organization - in engineering, industry, systems engineering, software, IT, the service sector and beyond. * Provides detailed, practical and innovative coverage of key subjects including requirements specification, design evaluation, specification quality control and evolutionary project management * Offers a complete, proven and meaningful 'end-to-end' process for specifying, evaluating, managing and delivering high quality solutions * Tom Gilb's clients include HP, Intel, CitiGroup, IBM, Nokia and the US Department of Defense.